2020
DOI: 10.3389/fpsyg.2020.01099
|View full text |Cite|
|
Sign up to set email alerts
|

Do Specific Pedagogies and Problem-Based Teaching Improve Student Employability? A Cross-Sectional Survey of College Students

Abstract: Higher education policy and manpower training have failed to meet the requirement of rapidly changing society and employers' expectation in Taiwan, resulting in a significant gap between university education and employment. Student employability should also be a focus of all higher education institutions, although whether a high degree of student learning outcomes can represent a high degree of student employability is still unclear. This study explores the relationships among pedagogy for employability, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Graduates who have accepted the problem-based teaching pattern could enhance their critical thinking and employment-related competencies (Baek and Cho, 2018 ; Liu et al, 2020 ); the design of learning context is highly correlated with employability and stimulates positive abilities. Similar research results like pedagogy for employability (POE) has a positive impact on students' absorptive capacity (AC; Li et al, 2020 ) and also proves the importance of educational practice, which enhances graduate employability of identifying, digesting, and applying the process into their available knowledge. Employability skills could also be developed through understanding the conditions and standards of the curriculum and teaching activities of teachers, which leads to the successful creation of flipped learning (Peng et al, 2021 ).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 59%
“…Graduates who have accepted the problem-based teaching pattern could enhance their critical thinking and employment-related competencies (Baek and Cho, 2018 ; Liu et al, 2020 ); the design of learning context is highly correlated with employability and stimulates positive abilities. Similar research results like pedagogy for employability (POE) has a positive impact on students' absorptive capacity (AC; Li et al, 2020 ) and also proves the importance of educational practice, which enhances graduate employability of identifying, digesting, and applying the process into their available knowledge. Employability skills could also be developed through understanding the conditions and standards of the curriculum and teaching activities of teachers, which leads to the successful creation of flipped learning (Peng et al, 2021 ).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 59%
“…Specifically, Problem-based learning students are able to actively respond to changing environments and new challenges. They are good at thinking out of the fixed way, thinking from multiple perspectives, mastering learning experience through problem solving and enhancing knowledge accumulation, which will enhance students' employability (Almulla, 2020;Peng et al, 2018;Li et al, 2020)also confirmed the above point of view. This study adopted structural equation model to analyze 553 undergraduates in Taiwan, and the results showed that problem-based learning had a significant positive impact on students' employability.…”
Section: The Moderator Of Job Market Knowledgementioning
confidence: 84%
“…As discussed above, problem-based learning involves improving students’ interests in learning and career paths (Clausen & Andersson, 2019 ; Li et al, 2020 ). When students have a highly proactive personality, they are more likely to have a sufficiently stable disposition to develop the appropriate learning attitudes and higher-order thinking skills needed to face real-world challenges in their future employment, e.g., critical thinking and reflection skills (White et al, 2004 ), which increases their positive attitude concerning being employable.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…The effectiveness adoption of case method coaching for problem-based learning will bridge the gap between education and employment, as business students will be more well prepared and capable to face the dynamic contemporary workplace environment. Hence, business students are expected to be more confident in solving workplace-based problems, demonstrate positive attitudes and prepare to overcome any challenges (Li et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%